PEMANFAATAN GOOGLE FORM UNTUK EVALUASI PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI MIM KEDUNGWULUH LOR - Asa Sumbawa Nur Dania; Sri Muryaningsih (Renjana Pendidikan Dasar, 2022)
Abstract: The study aims to determine the application of the use of the google form application to evaluate learning during the covid-19 pandemic in class IV B MIM Kedungwuluh Lor. This research is a type of qualitative descriptive research. The subjects in this study were the principal, teachers of class IV B and students class IV B at MIM Kedungeuluh Lor. Data collection techniques with observation, interviews and documentation. The data analysis used by the Miles and Huberman model is a data collcetion, data reduction, data display, conclusion drawing. Test the validity of the data using source triangulation techniques. The result showed that the use of the google form application for evaluation of learning during the covid-19 pandemic at MIM Kedungwuluh Lor had gone well and made it easier for the teacher to carry out evaluation activities. Google forms haveadvantages and disadvantages in their use, including saving costs, making it easier fot teacher to correct answers. The drawback is the limited google form design. Contraints in its utulization are related to the unsupported internet network an limited quota